Trial supports targeted radiotherapy for early breast cancer but protocol still requires 3 weeks of daily therapy - Vaidya, Jayant S.; Wenz, Frederik; Tobias, Jeffrey S. (Evidence based medicine, 2018)
Commentary on: Coles CE, Griffin CL, Kirby AM, et al . IMPORT Trialists. Partial-breast radiotherapy after breast conservation surgery for patients with early breast cancer (UK IMPORT LOW trial): 5-year results from a multicentre, randomised, controlled, phase 3, non-inferiority trial. Lancet 2017;390:1048-60. - - The evidence-based local treatment for early breast cancer is breast-conserving surgery and radiotherapy, requiring 3-6 weeks of daily whole breast external beam radiation therapy, which is inconvenient for patients and expensive. - - The suggestion that targeted radiation to the tumour bed with modern techniques may be adequate was proposed in 1995.1 This was heralded as a new standard2 with the publication of the TARGIT-A trial3 4 of single-dose targeted intraoperative radiotherapy (TARGIT-IORT), later confirmed by other European studies using brachytherapy5 that requires 5 days of inpatient stay or EBRT.6 - - In this study,7 in 30 UK centres, from 2007 …